Do business customers perceive what salespeople believe? Perceptions of salesperson adoption of innovations - Herbert Endres; Roland Helm; Christian Schmitz; Christine Hofstetter (Journal of Product Innovation Management, 2022)
A salesperson's commitment and effort toward an innovation can determine whether the customer agrees to buy it, such that customers' perceptions of such commitment and effort are critical. But these perceptions also might differ fundamentally from the salesperson's self-perceptions of commitment and effort. Therefore, this paper presents a theoretical framework of the relation between salesperson-perceived and customer-perceived commitment and effort, as exhibited by the salesperson while selling an innovation, which represents salesperson adoption. In the framework, job satisfaction factors also exert contingent, moderating effects. The authors gather unique, dyadic data from surveys of salespeople and their (potential) business customers during visits to sell a conventional, incremental innovation, complemented by objective purchase data gathered from company records. Three key insights emerge fromt this study. First, salespeople's own perceptions of their commitment and effort have only moderate influences on customers' perceptions of salespeople's commitment and effort. Second, customers seem to recognize salesperson effort more readily than salesperson commitment, although salesperson commitment has a higher sales performance impact than salesperson effort. Thus, sales managers should seek to encourage and support both the commitment of salespeople and also perceptions of that commitment among customers. Third, while a higher organizational support or job autonomy strengthens customers' perceptions of salesperson adoption, a higher pay satisfaction diminishes it. Thus, firms might need to find ways to increase the support for the salespeople and their autonomy and to reduce salespeople's satisfaction with their (direct) payments. In total, these findings suggest significant scientific and managerial implications.
Keywords: 650; commitment and effort; dyadic sample; emotional contagion; innovation adoption; innovation sales performance; job satisfaction factors; salesperson adoption; salesperson and (business) customer perception